Datos sobre fiebre reumática y cardiopatía reumática en el Perú - Subiria Carrillo, Ricardo (1950)
They have been studied 2016 cases of organic heart disease of which were 1349 hospitals and 667 patients were private patients. The percentage of cases of rheumatic heart disease in both groups was determined; 287 were selected rheumatic heart disease, in which 63 cases of rheumatic potential were added, making a total of 350 patients. In addition, a group of 632 young people was discussed at full fitness, considered representative of the general population of Peru. This material has served to an epidemiological and clinical study.